El test de Turing: dos mitos, un dogma - González, Rodrigo (Revista de Filosofía, 2007)
Debunking two commonly held myths and fleshing out its dogma, this article deals with the Turing Test, one of the most famous and controversial methods to assess the existence of mental life in the Philosophy of Mind. Firstly, I show why Turing never gave a definition of intelligence. Secondly, I dispute claims that the Turing Test provides a necessary or sufficient condition of intelligence. Thirdly, in view of its aim and the sort of evidence it offers, I consider whether or not Turing’s test can be regarded as a scientific experiment in light of Fodor’s theory. Finally, I argue that Turing is committed to a form of behaviourism and, further, confuses simulation -an epistemic process which, being governed by verisimilitude, is successful when someone is caused to believe that the computer is intelligent-with the duplication of intelligence qua property, which takes place at an ontological level. This confusion involves a dogma and explains why, despite being devised as the final solution to the dilemma of whether or not programmed machines think, the Turing Test has precisely had the opposite effect for longer than five decades, stimulating the philosophical discussion on the nature of mind.